THE EFFECTIVENESS OF AN INTEGRATED ASSESSMENT TO IMPROVE THE STUDENTS’ ENGLISH GRAMMAR ABILITY - Refnita, Lely (English Department FBS UNP, 2012)
This article is a part of the writer’s dissertation on the development of an integrated English grammar assessment. Although some say that English grammar is not needed when someone speaks and/or writes English, it was found that incorrect use of grammar disturbed the communication. It is also believed that having good English is a must when someone wants to be a model. Standing on this position, the writer had carried out an experiment on giving an integrated assessment to train her students who will be future English teachers to develop their English grammar ability. The research was carried out in the form of an experimental research by using a one-group pretest posttest design. The sample comprised all the first year students of English Department of Bung Hatta University, Padang, West Sumatera. The research result showed that the assessment did not only help the students write more sentences, but it also helped them write more number of grammatically correct sentences. The data analysis revealed that the students improve their achievement. It was shown by the increasing mean score from 26.43 in the pretest into 50.12 in the posttest. The analysis of significance also showed that the calculated-t value (18.9052) was much higher than the table-t value (1.9837). It indicated that the integrated assessment was effective to improve the students’ English grammar ability.